Electro-optic modulation using asymmetric Fabry-Perot laser diode amplifiers. - HEGARTY, JOHN (My University, 1994)
We report the use of laser diode amplifiers, whose facets have unequal mirror reflectivities, as asymmetric Fabry-Perot modulators. Due to the presence of optical gain in these devices we observe modulation of reflected light with both large absolute modulation depth and high contrast ratio.
PUBLISHED
Keywords: Physics; Physics